Genetic polymorphisms among and between blast disease resistant and susceptible finger millet, Eleusine coracana (L.) Gaertn. Issue 4 (8th March 2016) - Saha, Dipnarayan; Rana, Rajeev Singh; Arya, Lalit; Verma, Manjusha; Gowda, M. V. Channabyre; Upadhyaya, Hari D.
Abstract: Fungal blast disease is one of the major constraints in finger millet production. Breeding for disease resistance in finger millet, needs characterization of genetic polymorphism among and between the resistant and susceptible genotypes. In total, 67 finger millet genotypes, which are resistant or susceptible to fungal blast disease, were analysed using sequence-related amplified polymorphism (SRAP) and simple sequence repeat (SSR) markers to assess genetic variations and select diverse parents. Twelve each of SRAP and SSR primers produced 95.1 and 93.1% polymorphic bands and grouped them into unweighted pair-group method with arithmetic average clusters. Two of the finger millet genotypes, IE 4709 (blast resistant) and INDAF 7 (susceptible) were distinguished as most diverse genotypes as parents. Several genotype-specific bands observed with SSR primers are potential in developing genotype-specific markers. A high genetic diversity within the resistant and susceptible genotypes, rather than between them, was revealed through Nei's gene diversity ( h ) index and analysis of molecular variance. The finding helps us to understand the extent of genetic polymorphism between blast disease resistant and susceptible finger millet genotypes to exploit in resistance breeding programs.